Pengaruh Metode Latihan Drill Terhadap Ketepatan Pukulan Backhand Clear Pada Siswa Ekstrakurikuler Bulutangkis SMK Negeri 3 Jepara - Riza Indra Dwijaya; Galih Dwi Pradipta; Setiyawan Setiyawan (Journal of Physical Activity and Sports (JPAS), 2020)
This research is based on the lack of ability to roll the backhand of badminton extracurricular students at SMK Negeri 3 Jepara because the backhand style is still difficult and they are not used to the variation of punch training and have never been given special training by the coach. The purpose of this study was to determine all the effects of training exercises on the accuracy of the back strokes of badminton extracurricular students at SMK Negeri 3 Jepara. This research was conducted with a quantitative approach. The design of this study is a Quasi Experiment with the method of The Untreated Control Group Design with Pretest and Posttest with data retrieval using tests. The population in this study was 30 students and the sample was taken by purposive sampling or with certain provisions as many as 16 students and divided into 2 groups, namely group 1 as treatment recipient and group 2 without treatment. The data technique uses the treatment of the drill training method. The data analysis technique used in this study was the prerequisite test, including the normality test, homogeneous test, and hypothesis testing. The results of the study indicate that the training method affects the accuracy of rolling backhand badminton extracurricular students of SMK Negeri 3 Jepara from group 1 with an average of 22.5 and a value of 10.828> t table 2.145 and a significance value of 0.000 <0.05, with a percentage increase of 13, 47%, while for group 2 without treatment with an average of 19,625 which is only 8.47% with an average difference of 3,875 posttest. The anatomical results of the training method also have an effect on increasing the students' body movements, because the body stimulates the body with fast movements so that the student's body becomes accustomed to doing backhand clear strokes. It can be rejected that the hypothesis h1 is accepted there is an effect of the drill training method on the accuracy of rolling backhand clear at SMK Negeri 3 Jepara is accepted.   Keywords: Keywords: backhand clear, drill practice, accuracy Abstrak Penelitian ini di latar belakangi oleh kurangnya kemampuan pukulan backhand clear siswa ekstrakurikuler bulutangkis SMK Negeri 3 Jepara dikarenakan pukulan backhand dianggap masih sulit dan belum terbiasa juga kurangnya variasi latihan pukulan dan belum pernah diberikan latihan secara khusus oleh pelatih. Tujuan penelitian ini untuk mengetahui seberapa besar pengaruh latihan drill untuk ketepatan pukulan backhand clear siswa ekstrakuriler bulutangkis SMK Negeri 3 Jepara. Penelitian ini dilakukan dengan pendekatan kuantitatif. Desain penelitian ini adalah Quasi Experimen dengan metode The Untreated Control Group Design with Pretest and Posttest dengan pengambilan data menggunakan tes. Populasi dalam penelitian ini adalah 30 siswa dan diambil sampel dengan purposive sampling atau dengan ketentuan tertentu sebanyak 16 siswa dan dibagi menjadi 2 kelompok yaitu kelompok 1 sebagai penerima treatment dan kelompok 2 tanpa treatment. Teknik pengumpulan data menggunakan treatment metode latihan drill. Teknik analisis data dalam penelitian menggunakan uji prasyarat antara lain uji normalitas, uji homogeny, dan uji hipotesis. Hasil dari penelitian menunjukan bahwa metode latihan drill berpengaruh terhadap ketepatan pukulan backhand clear siswa ekstrakurikuler bulutangkis SMK Negeri 3 Jepara dari kelompok 1 dengan rata-rata 22,5 dan nilai thitung 10,828 > ttabel 2,145 dan nilai signifikansi 0,000 < 0,05, dengan peningkatan presentase 13,47%, sedangkan untuk kelompok 2 tanpa perlakuan dengan rata-rata 19,625 yang hanya sebesar 8,47% dengan selisih rata-rata posttest 3,875. Hasil secara anatomi metode latihan drill juga berpengaruh dalam peningkatan pergerakan tubuh siswa, karena rangsangan tubuh dengan gerakan cepat sehingga gerak tubuh siswa menjadi terbiasa dalam melakukan pukulan backhand clear.Dapat disimpulkan bahwa hipotesis h1 diterima yaitu ada pengaruh metode latihan drill terhadap ketepatan pukulan backhand clear SMK Negeri 3 Jepara diterima... Kata kunci: backhand clear, latihan drill, ketepatan